PROMOTING CHARACTER EDUCATION: AN ANALYSIS OF MORAL VALUES EMBODIED IN CHILDREN'S BOOK EIGHT O'CLOCK TALES BY ENID BLYTON - Sutari, Velentina Rizki (2014)
the present study entitledpromotingcharacter education: an analysis of moral values embodied in children's book eight o'clock tales(2008) by enid blytonfocuses on moral valuespromoted in the children's book. the aim of the study is toinvestigate the moral values in the children's book which is suitable with the values mentioned in 2013 indonesia curriculum. qualitative descriptive method which is supported by textual analysis approach was employed to analyze the data by referring to a theory of educational values by thomas lickona (1991). the results of data analysis show that some moral values embodied in the children's book as mentioned in curriculum 2013 are as the following:honesty, discipline, responsibility, being polite, care, teamwork, peace (care for peace), being confidentto interact with families, friends, teachers, and neighbors, and being responsiveand proactive were found. however, the moral values i.e. patriotism and tolerance were not found. therefore, eight o'clock tales(2008)could berecommended as one of english educational materials or resourcesforelementary and junior high school students since it promotes the character education which is embodied in the book appropriately. keywords: moral values, children's book,character education, 2013 indonesia curriculum.